2006
DOI: 10.1001/jama.295.13.1549
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity in the United States, 1999-2004

Abstract: The prevalence of overweight among children and adolescents and obesity among men increased significantly during the 6-year period from 1999 to 2004; among women, no overall increases in the prevalence of obesity were observed. These estimates were based on a 6-year period and suggest that the increases in body weight are continuing in men and in children and adolescents while they may be leveling off in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

180
5,450
40
152

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 7,879 publications
(5,822 citation statements)
references
References 11 publications
180
5,450
40
152
Order By: Relevance
“…2 More recent data continued to demonstrate an increase in the prevalence of obesity in children, adolescents, and adults between 1999 and 2004 in the United States. 3 Epidemiological data on obesity in Asia are comparatively less complete, and Gu et al 4 reported the age-standardized prevalence of overweight (BMIX25.0) to be 26.9% (25.7-28.1) in men and 31.1% (29.7-32.5) in women in China. In Hong Kong, 39.2% of the population was found to be obese (BMI X25.0).…”
Section: Introductionmentioning
confidence: 99%
“…2 More recent data continued to demonstrate an increase in the prevalence of obesity in children, adolescents, and adults between 1999 and 2004 in the United States. 3 Epidemiological data on obesity in Asia are comparatively less complete, and Gu et al 4 reported the age-standardized prevalence of overweight (BMIX25.0) to be 26.9% (25.7-28.1) in men and 31.1% (29.7-32.5) in women in China. In Hong Kong, 39.2% of the population was found to be obese (BMI X25.0).…”
Section: Introductionmentioning
confidence: 99%
“…4 Genetic and environmental factors are of importance for the development of obesity and T2D, as higher prevalences are found in certain ethnic groups and are associated with lower socioeconomic status. [5][6][7] In 15-to 19-year-old Pima Indians from Arizona, 5.1% were diagnosed with T2D, 8 and in a US cohort of eighth-grade students, who were predominantly minority, the prevalence of impaired glucose regulation and T2D reached 440%. 9 For most European countries, population-based data on T2D prevalence in youth are not available, so that it is currently unknown whether the situation is similarly alarming in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…However the recent increase in the rate of overweight and obesity, up to two thirds of the US population, may diminish the favorable effect of recent improvements in the diagnosis and treatment of CAD (2)(3)(4).…”
mentioning
confidence: 99%
“…However, direct measures of region-specific adipose tissue are superior to estimated overall adiposity for the identification and management of high-risk individuals (2)(3)(4)9).…”
mentioning
confidence: 99%